Aerodynamic optimization using passive control devices near the bogie cabin of high-speed trains - Yao, Yongfang; Sun, Zhenxu; Li, Guibo; Yang, Guowei; Prapamonthon, Prasert; Guo, Yi; Wang, Mengying (My University, 2022)
Bogies are responsible for a significant amount of aerodynamic resistance and noise, both of which negatively affect high-speed train performance and passenger comfort. In the present study, the passive control method is applied in designing the bogie cabins of a high-speed train to improve its aerodynamic characteristics. Two passive control measures are introduced, namely, adding a spoiler and creating diversion grooves near the bogie cabins. Furthermore, the aerodynamic and aeroacoustic characteristics of a high-speed train operating at 350 km/h under different control strategies are numerically investigated using the improved-delayed-detached-eddy simulation (IDDES) and the acoustic finite element method (FEM). The impacts of passive control devices on drag reduction, slipstream, and aerodynamic noise are presented and discussed. Numerical results reveal that the passive control devices have a major effect on the slipstream around the train. The amplitude of the fluctuating pressure is higher in the first half of the train than in the second half. The first bogie has the maximum amplitude of the acoustic pressure for both the train with and without passive devices. In the far field, the spoiler installation and placement of the diversion grooves in the front of the bogie cabin can significantly reduce aerodynamic drag and noise. Hence, as shown in this study, using passive control methods to improve the aerodynamic and aeroacoustic properties of high-speed trains can be a viable option. [Figure not available: see fulltext.].
Keywords: Aerodynamic drag; Aerodynamic noise; High-speed trains; Passive control devices; Slipstream